FAKTOR-FAKTOR YANG MEMENGARUHI INDEKS HARGA SAHAM (Media Riset Akuntansi, 2022)
The research was intended to analyze how much influences of the Dow Jones index, Nikkei 225 index and Hang Seng index against Composite Stock Price Index. The population of this study is the Dow Jones index, Nikkei 225 index, Hang Seng index and Jakarta Composite Index from 2013 – 2016. Samples were selected by purposive sampling method using monthly adjusted closing data during January 2013 through June 2016. This research used multiple linear regression analysis to find out the effect of independent variables to dependent variable. The result shows that partially the Dow Jones indeks and Nikkei 225 index influence the Composite Stock Price Index significantly. The Hang Seng index does not significantly influence the Composite Stock Price Index. Overall Dow Jones indeks, Nikkei 225 indeks and Hang Seng index have significant effect to Composite Stock Index. This suggests external factors which are the movement of stocks in America, Japan and Hong Kong have an influence on the Composite Stock Price Index at IDX.